Penerapan Strategi Akuntansi Lingkungan dan Inovasi Hijau untuk Mencapai Keberlanjutan Bisnis UMKM Melalui Peningkatan Kinerja Lingkungan - Khairina Nur Izzaty; Grace Tianna Solovida (ITB AAS Indonesia Surakarta, 2025)
Sustainability of business that is the focus of stakeholders can be achieved by increasing economic profit, reducing environmental impact, and social prosperity. A more environmentally oriented business can increase public trust. This study aims to obtain empirical evidence regarding the role of environmental performance as a mediator of the influence of environmental accounting strategies and green product innovations on the sustainability of MSME businesses. The sample of this study was MSME actors in the manufacturing or processing sector in Semarang City. The research method used was quantitative with primary data in the form of a survey that would be analyzed using a structural equation model. The results of the hypothesis test showed that environmental accounting strategies had no effect on environmental performance, while green innovation had a significant positive effect on environmental performance. For testing direct effects, environmental accounting strategies and green innovations did not have a direct effect on the sustainability of MSME businesses. Environmental performance had a significant positive effect on the sustainability of MSME businesses. From the mediation test, environmental performance was proven to mediate the effect of green innovation on the sustainability of MSME businesses, but could not mediate the effect of environmental accounting strategies on the sustainability of MSME businesses. The results of this study are expected to contribute to the sustainability of MSME businesses by paying more attention to the quality of the products and the environment in which the business operates.